THE EFFECT OF PUSH, PULL AND MOORING FACTORS TO SWITCHING INTENTION OF POST-PAID ELECTRICAL CUSTOMER’S TO PREPAID ELECTRICAL - Mirna Erviana Isnitahnia; Karnowahadi Karnowahadi; Isnaini Nurkhayati (Politeknik Negeri Semarang, 2019)
Prepaid electricity is expected to increase customers’ satisfaction and reduce the overdue payments of postpaid electricity customers each month, but until 2019 the number of customer who switch to using prepaid electricity is still low in Klaten City. This research was conducted to determine the effect of push, pull and mooring factors on switching intention postpaid electricity customers to prepaid at PT PLN (Persero) ULP Klaten Kota. The data that used are primary data obtained using a quetionarry, interview and literature review. The sample in this study were 100 person that is prepaid electricity customers who had used postpaid electricity. Sampling is done by using non probability sampling method that is incidental sampling. The analytical model used is multiple linear regression analysis. The ressult of the coefficient of determinan (Adjusted R Square) showed that 41,2% switching intention customers is influenced by push, pull and mooring factors. The rest was explained by other factors not examined in this study. The result of hypothesis testing show that push, pull and mooring factors together have a significant possitive effect, partially pull and mooring have a significant possitive effect while the push factor have an possitive effect but not significantly on switching intention customer of PT PLN (Persero) ULP Klaten Kota.